2013
DOI: 10.2169/internalmedicine.52.9205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Classification of Subgroups According to the Rome III Criteria Cannot be Used to Distinguish the Associated Respective Pathophysiology in Japanese Patients with Functional Dyspepsia

Abstract: Objective Patients who meet the Rome III criteria for functional dyspepsia (FD) are generally classified into the following two subgroups, those with postprandial distress syndrome (PDS) and those with epigastric pain syndrome (EPS), in order to treat the dyspeptic symptoms caused by the respective pathophysiological conditions. However, whether simple classification of FD can accurately distinguish the pathophysiological differences between PDS and EPS remains to be clarified because the pathophysiology of FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
3
11
1
Order By: Relevance
“…In addition, while GI function during nighttime should be active due to food absorption and other physiological functions, in the present study it was diminished, implying impaired excretory function as a result of diminished food digestion or GI motility. Previous studies have reported that delayed gastric emptying is involved in 30–60% of FD cases, ( 25 27 ) and the findings of the present study appear to support this assertion. As an event capable of altering ANS function, meals typically trigger an increase in parasympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, while GI function during nighttime should be active due to food absorption and other physiological functions, in the present study it was diminished, implying impaired excretory function as a result of diminished food digestion or GI motility. Previous studies have reported that delayed gastric emptying is involved in 30–60% of FD cases, ( 25 27 ) and the findings of the present study appear to support this assertion. As an event capable of altering ANS function, meals typically trigger an increase in parasympathetic nervous system activity.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, disturbed gastric accommodation and gastric emptying might drive PPDS. However, studies evaluating the role of these putative pathophysiological mechanisms among FD subtypes have shown conflicting results [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Ochi M et al also did not find any association of delayed gastric emptying in the two groups of functional dyspepsia pointing to different mechanism for PDS. 14 This is supported by a recent study by Vanheel et al 15 where visceral hypersensitivity was closely associated with PDS. Further they did not find any difference between the Rome-III subgroups in the prevalence of gastric hypersensitivity, impaired gastric accommodation and delayed gastric emptying.…”
Section: Discussionmentioning
confidence: 56%